Cardiovascular Events in Adults With Community Acquired Pneumonia (KYAMC Journal, 2020)
Background: Community-acquired pneumonia (CAP) is the most frequent infectious disease, responsible for significant morbidity and mortality world wide. Poor outcome in CAP patients is directly related to pneumonia also to comorbidities both during hospitalization and long term after discharge.Objective: To determine the incidence of major cardiac complications in CAP patients.Materials and Methods: This observational study was conducted in Medicine Department, Gazi Medical College and Hospital (GMCAH) Khulna from January 2016 to March 2019. We studied patients with association of CAP and ACE on admission or Patients with CAP on admission, developing ACE after 48 to 72 hours of hospital stay. Patients who were admitted with ACE but developed a CAP after 48 to 72 hours of admission and Patients with severe sepsis with a concomitant elevated troponin were excluded from the study.Results: Out of 1406 patients with CAP, 12.4% presented with cardiovascular events and 87.6% without cardiovascular events. In cardiovascular events, 79.3% patient had heart failure, 17.8% had cardiac arrhythmia and 2.9% had myocardial infarction. Subjects with hyperlipidemia had 2.10 fold more cardiac events than subjects without hyperlipidemia. A Subject with (PSI) 80 had 3.16 (95% CI 1.18 to 8.47) times increase in odds having cardiovascular events. Hyperlipidemia and PSI were significantly associated with cardiovascular events.Conclusion: Major cardiac complications occur in a substantial proportion of patients with CAP. Physicians and patients need to appreciate the significance of this association for timely recognition and management of these events. Strategies aimed at preventing pneumonia in high-risk population need to be optimized.KYAMC Journal Vol. 10, No.-4, January 2020, Page 191-195